2012
DOI: 10.1111/j.1365-2419.2012.00614.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ontogenetic trophic shift in two hake species, Merluccius capensis and Merluccius paradoxus, from the Northern Benguela Current ecosystem (Namibia) using stable isotope analysis

Abstract: Two species of hake, Merluccius capensis (MC) and Merluccius paradoxus (MP), together account for most of Namibia’s fisheries catch and they are collectively the most important secondary consumers in the Benguela Current ecosystem. To better resolve their feeding behavior in the northern Benguela Current ecosystem, we examined the size‐specific ontogenetic shift in MC and MP using stable isotopes of δ13C and δ15N as measures of relative source production and trophic level. We also compared hake isotope values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
3
15
0
Order By: Relevance
“…paradoxus is consistent with a nearshore–offshore depletion in 13 C of pelagic production. This was also observed by Iitembu et al () for the two Merluccius species off Namibia, and has been seen in other ecosystems (Miller et al , ). The higher δ 13 C in both Merluccius species off the south coast observed in this study, however, was contrary to what would be expected, given the higher upwelling and diatom‐based production off the west coast.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…paradoxus is consistent with a nearshore–offshore depletion in 13 C of pelagic production. This was also observed by Iitembu et al () for the two Merluccius species off Namibia, and has been seen in other ecosystems (Miller et al , ). The higher δ 13 C in both Merluccius species off the south coast observed in this study, however, was contrary to what would be expected, given the higher upwelling and diatom‐based production off the west coast.…”
Section: Discussionsupporting
confidence: 82%
“…capensis by Parkins (). Similarly, Iitembu et al () reported significant positive relationships between δ 15 N and size for both M . capensis and M .…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, stable isotope-based results indicated that small hake (20-39 cm) of both species were trophically indistinguishable at about 3.3, indicating predominant zooplanktivory. The trophic levels of M. capensis and M. paradoxus of 60-70 cm were estimated at 3.4-3.6 and 3.7-3.8, respectively (Iitembu et al, 2012).…”
Section: Diet and Trophic Relationshipsmentioning
confidence: 99%